Calprotectin may be positively associated with the severity of acne vulgaris - Shireen A. Al-tameemi; Zainab S. Abid; WenChieh Chen; Fawwaz Alshammri; Hussein Abid (Baghdad Journal of Biochemistry and Applied Biological Sciences)
Background and objective: Acne vulgaris (AV) is a common skin disease of sebaceous hair follicles. Many factors are associated with the occurrence and severity of acne, while the exact etiology remains incompletely understood. The current study was aimed to investigate the association between the severity of acne and serum zinc, copper, and calprotectin.